LANGUAGE DEVELOPMENT IN STUDY ABROAD (SA) CONTEXT AND RELATIONSHIP WITH INPUT AND INTERACTION IN SLA - suryani suryani (Englisia: Journal of Language, Education, and Humanities, 2015)
Language learning can occur anytime and anywhere (context). In term of context, language learning can take place whether at home context or at a study abroad context. This article presents the necessary background to existing literature and previous research about language development in various contexts, more specifically in a study abroad (SA) context. Language learners who are studying abroad can lead to language development from a number of perspectives. Research findings revealed that language development can take a variety of forms including grammar, vocabulary, fluency, communicative skill, etc. These research findings will be reviewed in order to have a clear understanding about this issue. Then, this article continues to give a brief explanation on the role of input and interaction in SLA with some views on it.